2019
DOI: 10.3390/ijms20205155
|View full text |Cite
|
Sign up to set email alerts
|

Verification of 5-Aminolevurinic Radiodynamic Therapy Using a Murine Melanoma Brain Metastasis Model

Abstract: Melanoma is a highly aggressive cancer with a propensity for brain metastases. These can be treated by radiotherapy, but the radiation-resistant nature of melanoma makes the prognosis for melanoma patients with brain metastases poor. Previously, we demonstrated that treatment of mice with subcutaneous melanoma with 5-aminolevurinic acid (5-ALA) and X-rays in combination, (“radiodynamic therapy (RDT)”), instead of with 5-ALA and laser beams (“photodynamic therapy”), improved tumor suppression in vivo. Here, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…For these reasons, 5-ALA, and not PpIX, is considered a radiosensitizer and is used in clinical practice and has been evaluated as a precursor in radiosensitized animal models. In this in vitro study, DSBs in melanoma cell nuclei were confirmed by γH2AX by X-ray irradiation and further enhanced by PpIX, as well as 5-ALA treatment in a previous study [8]. Further, the DSBs were accompanied by a decrease in cell surviving fraction, indicating that DNA damage enhanced by PpIX is one of the causes of anticancer activity.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…For these reasons, 5-ALA, and not PpIX, is considered a radiosensitizer and is used in clinical practice and has been evaluated as a precursor in radiosensitized animal models. In this in vitro study, DSBs in melanoma cell nuclei were confirmed by γH2AX by X-ray irradiation and further enhanced by PpIX, as well as 5-ALA treatment in a previous study [8]. Further, the DSBs were accompanied by a decrease in cell surviving fraction, indicating that DNA damage enhanced by PpIX is one of the causes of anticancer activity.…”
Section: Discussionsupporting
confidence: 72%
“…A series of studies on the combination treatment of 5-ALA and ionizing radiation has been conducted by some research groups, and 5-ALA with subsequent intracellular PpIX accumulation has been found to increase kilo electron volt (KeV) or mega electron volt (MeV) irradiation cytotoxicity in a variety of contexts using mouse models of melanoma, glioma, colon cancer, etc. [5][6][7][8][9][10][11][12][13][14][15]. PpIX expression enhances ROS generation, which increases cellular DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] It is worth mentioning that some of the published literature uses the term radiodynamic therapy (RDT) referring to the situation where ionizing radiation (X-ray) is used to excite a sensitizing agent. [40][41][42] This term tends to be used when the sensitizing agent is a molecule. Here, we will use the term X-PDT referring to the use of X-rays to excite sensitizing agents regardless of their molecular or NP character (see Section 7 for more clarifications of terminology used in this field).…”
Section: Introductionmentioning
confidence: 99%
“…This novel fluorescent labeling has the potential to be widely applied in various studies, e.g., in super-resolution microscopy, in basic biology, and in X-ray radiotherapy of cancer cells [ 60 , 61 ], by exploiting the X-ray induced radicals, and also to radiotherapy using electrons, electron beam lithography for fine processing technologies and nanomaterials constructions, and to achieve the precise post modification of materials. In the future, this labeling might be further developed as an important research and clinical probe for the diagnoses of diseases due to high spatial resolution fluorescence labeling.…”
Section: Discussionmentioning
confidence: 99%